2013
DOI: 10.1111/hdi.12076
|View full text |Cite
|
Sign up to set email alerts
|

Creation of arteriovenous fistulae for hemodialysis in octogenarians

Abstract: Elderly patients, defined as octogenarians and nonagenarians, are an increasing population entering renal replacement therapy. Advanced age appears as an exclusive factor negatively influencing dialysis practice. Elderly patients are referred late for the initiation of hemodialysis and more likely are offered catheters rather than arteriovenous fistulae (AVF), which increase mortality and negatively affect quality of life. We present our approach to the creation of vascular access for hemodialysis in this dema… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 24 publications
1
14
0
Order By: Relevance
“…According to our data patients over 80 years tend to have even slightly less shunt complications than younger patients. Neither did other authors find differences in the elderly [21,22], and especially in patients aged over 80 years [23,24]. Nadeau-Fredette et al reported a higher rate of primary AV-fistula failure in patients over 80 years.…”
Section: Discussionmentioning
confidence: 99%
“…According to our data patients over 80 years tend to have even slightly less shunt complications than younger patients. Neither did other authors find differences in the elderly [21,22], and especially in patients aged over 80 years [23,24]. Nadeau-Fredette et al reported a higher rate of primary AV-fistula failure in patients over 80 years.…”
Section: Discussionmentioning
confidence: 99%
“…These observations may potentially be explained by the poorer long-term patency and higher risk of complications of AVGs versus AVFs, including thrombosis and infection, leading to a greater number of secondary interventions that may carry potential risk in elderly hemodialysis patients [45,46]. Given that age has not been found to be a potent determinant of AVF patency across multiple studies [47][48][49][50], it may be inferred from our data that AVF should remain as the preferred vascular access type in this population. However, among patients in whom there may be a delay in placement of an AVF from a CVC due to poor maturation or primary access failure, given the high mortality risk observed with a longer duration of CVC use, AVGs may need to be considered as a viable option.…”
Section: Discussionmentioning
confidence: 78%
“…But this assumption lacks evidence. Other authors did not find differences in the elderly [17,18] , and especially not in patients aged over 80 years [19,20] . Nadeau-Fredette et al [21] reported a higher rate of primary AV-fistula failure in patients over 80 years.…”
Section: Discussionmentioning
confidence: 80%